An efficient deep learning approach for detecting Alzheimer’s disease using brain images - Sani, Mehedi Hasan; Rahman, Mohibur; Achib, Md. Abdullah Al; Hossain, Rakib (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.